THE CORRELATION BETWEEN STUDENT’S HABIT IN WATCHING ENGLISH MOVIE AND VOCABULARY MASTERY AT THE SECOND YEAR OF SMAN 1 ANGGERAJA - Dahniar Badruddin; Masyhud Zainuddin (ETERNAL (English, Teaching, Learning and Research Journal), 2016)
The objective of this research was to find out whether there is a correlation between students’ habit in watching English movie and vocabularymastery at the second year of SMAN 1 Anggeraja in the academic year 2015/2016. This study is a correlation research. The instruments used were questionnaire and vocabulary test. The result of the analysis showed that there was significant correlation between students’ habit and vocabulary mastery in watching English movie to 0.766 at the significant level of 0.05 with the critical value of r table 0.339. The correlation between students’ habit in watching English movie and vocabulary mastery was significant since the coefficient correlation is higher than the critical value of r table (0.766 > 0.339). It means that there is a significant correlation between students’ habit in watching English Movie and Vocabulary Mastery at the Second Year of SMAN 1 Anggeraja.